The Role of Imaginative Fairy Tales in Reading Literacy - Chandra Chandra; Muhammad Habibi; Ari Suriani; Annisa Kharisma (Jurnal Basicedu, 2021)
The School Literacy Movement program in Indonesia which has been run in elementary schools was still minimal with current reading resources, less inviting students to think ahead, and developing a monotonous attitude. It was necessary to produce the latest children's reading books such as imaginative tales that present stories related to technological developments. Producing imaginative fairy tales was the aim of this research. The study was conducted using a mixed-method with the Plomp development model. The Plomp development model has three steps: preliminary research, prototyping phase, and assessment stage. The research results at the preliminary research that students like imaginative tales and need new stories every morning before learning begins. In the prototyping phase is produced a valid and practical imaginative fairy tale book. Imaginative fairy tale book was designed using the Adobe Photoshop program. The imaginative fairy tale book that was developed was able to provide new ideas for students who read it. Besides, the development of a positive attitude is also included in the story, making it easier for teachers to educate students in elementary school